Improving the quality of care for female rape survivors at Scottish Livingstone Hospital, Molepolole, Botswana: A quality improvement cycle - Orleans A. Debley; Zelra Malan (AOSIS, 2020)
Background: Rape is prevalent in Botswana, but there has been limited research undertaken to improve the quality of healthcare for female rape survivors in this clinical setting. Research can not only influence the health outcomes of victims but also has the potential to inform policy. Aim: The aim of this study was to improve the quality of care for female rape survivors in Scottish Livingstone Hospital, Molepolole, Botswana. Setting: The setting is Scottish Livingstone Hospital, Molepolole, Botswana. Methods: This study was a qualitative cycle, using the normal steps of performing a baseline audit of clinical practice, planning and implementing changes and re-audit. Results: A total of 124 patient records were audited, comprising 62 patient records at baseline and re-audit. The mean age of victims was 23 years and the age category with the highest incidence of rape ranged between 12 and 20 years, constituting 47% of patients' records. During the baseline audit, only one out of 10 structural standards was met, while at re-audit eight structural standards were fully met. Although none of the process standards were met during both audits, statistically significant improvements in performance (p 0.05) were shown in six out of 10 criteria at re-audit. Conclusion: The quality of care for female rape survivors is suboptimal in our setting. However, simple interventions to improve the structure in place for patients and upskilling the entire practice team to align care to current international standards can improve the overall quality of healthcare.